Hand Eczema: Diagnostic Approach and Management - Oktarina, Caroline; Agustin, Triana; Legiawati, Lili; Budianti, Windy Keumala (Journal of Pakistan Association of Dermatologists, 2022)
Hand eczema (HE) is a chronic inflammatory disorder of the hand with a prevalence of 14.5% worldwide. The incidence of HE has increased considerably during Coronavirus-19 (COVID-19) pandemic due to increased hand hygiene practice. Despite not affecting the mortality rate, HE can decrease the patient’s quality of life significantly and increase morbidity. In general, HE can be classified based on its onset, etiology, precipitating factors, and clinical morphology. The diagnosis of HE is established through history taking and physical examination, however, several diagnostic tests should be performed to identify the etiology and exclude the differential diagnosis, including dermoscopic examination, histopathological examination, patch test, and prick test. In addition to diagnostic tests, the severity of HE should also be established to determine the appropriate therapy and monitor the therapeutic responses. After HE is identified, comprehensive management should be provided immediately so that HE will not progress into a chronic disorder which will further decrease the patient’s quality of life.